CEFERINO NAMUNCURÁ, BEATO MAPUCHE. - Valenzuela, Eduardo (Humanitas (07172168))
Ceferino Namuncurá was a young Salesian of Mapuche origin who has been venerated as a saint in the Argentine and Chilean Patagonia. His sanctuary in Chimpay, Río Negro, attracts thousands of people and his miraculous image is widely known. Ceferino desired to become a priest and evangelize his own people, but he couldn't enter the seminary due to possible canonical prohibitions or his delicate health. The Salesians, led by Don Bosco and Cardinal Cagliero, carried out missions in Patagonia and educated Ceferino. After his death in 1905, his remains were repatriated to Argentina and now rest in San Ignacio, where he has become a popular saint revered by the community. His figure represents Salesian youth spirituality and has left a mark on the imagination of the Argentine pampas.